Growth parameter acquisition and geometric point cloud completion of lettuce - Lou, Mingzhao; Lu, Jinke; Wang, Le; Jiang, Huanyu; Zhou, Mingchuan (Frontiers in Plant Science, 2022)
The plant factory is a form of controlled environment agriculture (CEA) which is a promising solution to the problem of food security worldwide. Plant growth parameters need to be acquired for process control and yield estimation in plant factories. In this paper, we propose a fast and nondestructive framework for extracting growth parameters. Firstly, ToF camera (Microsoft Kinect V2) is used to obtain the point cloud from the top view, and then the lettuce point cloud is separated. According to the growth characteristics of lettuce, a geometric method is proposed to complete incomplete lettuce point cloud. The treated point cloud has a high linear correlation with the actual plant height (R^2 =0.961), leaf area (R^2 =0.964), and fresh weight (R^2 =0.911) with a significant improvement compare to untreated point cloud. The result suggests our proposed point cloud completion method have the potential to tackle the problem of obtaining the plant growth parameters from a single 3D view with occlusion.